Editorial - Prado, Gilbertto; Nesteriuk, Sérgio (DAT Journal, 2024)
In this issue of the DATJournal, in addition to the texts selected regularly by the journal, we have one additional dossier. The dossier of this DATJournal has guest editor Guilherme Altmayer that presents design research at the Graduate Program at Universidade do Estado do Rio de Janeiro (PPDESDI/UERJ). This dossier continues the DATJournal special series on Postgraduate Programs in Design in Brazil, which are invited to present their trajectories, characteristics and strength lines. With this initiative, we intend, more than mapping and celebrating the strength and diversity of these Programs, to stimulate the exchange between Postgraduate Programs in Design in Brazil. We appreciate all contributions and wish you a good reading.